Comparative Analyses of The Islamic System with Other Economy System in The World - Awan, Ayesha; Ali, Wajahat; Ur Rehman, Hafiz Khalil; Idrees, Sadia (Pakistan Journal of Humanities and Social Sciences, 2023)
There are rumours that Islamic economic systems exist in developed nations with sizable Muslim populations. I have made an effort to regard the Islamic economic system primarily as a theoretical construct to organize the perspectives of many Islamic social philosophers on various significant concerns with other economic structures. The Holy Quran and modern science serve as their respective grounds, regardless of the many theories linked to these beliefs. In this article, we tried to distinguish between various economic systems, keep concepts straightforward, and explain them all. One of the traits of the capitalist economy is the free competition between suppliers and consumers. The core idea of socialism is a socioeconomic system in which social control owns both money and property. Poverty is one of socialism's unfavourable side effects, despite its ideals encouraging and facilitating corruption at the highest echelons of want-to-be regimes. The unbridled competition of the capitalist system benefits the wealthy while the unfortunate are exploited and endure. Due to its structured and particular knowledge sources, the Islamic economic system, in comparison, is independent of Islamic society, the Islamic state, and even the Islamic people. Islam successfully controls people completely, provides means for them to safeguard their property rights, and promotes both the acquisition of property and the development of moral prosperity. The Islamic economy requires sound management now more than ever. Due to these reasons, the Islamic economic system is a strong candidate to replace both capitalism and socialism. The comparative technique was applied in this essay. In contrast to "the dynamism of capitalism" and "the egalitarianism of socialism," the argument goes, the Islamic economic system has created positive outcomes. This study suggests those countries implement the Islamic economic model because it has been scientifically demonstrated to be superior to other systems. This research imparts an insight to academicians, aspiring researchers, and decision-makers.